Starting of three phase permanent magnet synchronous motor using BLDC motor driven - Darwati, Endang (Jurusan Teknik Elektro, Politeknik Negeri Bandung, 2024)
Three phase permanent magnet motor has many advantages including simple construction that makes it easy to maintain, has dynamic performance, high power density, reliability and durability. Permanent magnet motors can be operated as stepper motors, brushless direct current motor (BLDCM) and synchronous motor without having to change the three-phase driver motor circuit. The BLDCM are supplied with square or trapezoidal voltages, while the synchronous motor are supplied with sinusoidal voltages. The synchronous motor have advantages in terms of torque and power efficiency but cannot operate from a stationary condition, so it requires starting techniques to run it. The starting technique in this paper is the motor initially operated as the BLDCM until it approaches the desired synchronous frequency then moves into the synchronous generator for a while and then becomes the synchronous motor. The frequency of the motor and the phase difference between the stator field and the rotor field are critical points for this operating displacement. When the stator field precedes the rotor field, the displacement is smooth and the displacement time is very short, that is 1 second. Whereas when the stator field is left behind from the rotor field, the motor experiences a moment of jerking during its displacement and takes 3 seconds.